The distribution of zooplankton in the southern ocean and its dependence on the circulation of water - Voronina, N. M. (Sarsia, 1968)
The distribution of zooplankton in the Southern Ocean depends on seasonal changes in quantity and on redistribution of the plankton by currents. In the upper 100 m the meridianal component of the current shifts the maxima of some species northwards from the divergence zone at a mean velocity of about 20 cm/sec. In the Antarctic convergence zone the water sinks at a mean velocity of 10.5 m/day. This brings about an increase of the total plankton amounting to about 3% per day. As the southward flow of deep water is very slow the transfer of plankton in this layer is negligible.
Keywords: Sørishavet; marin biologi; oseanografi; plankton

Sperm whales of the Southeast Pacific. Part I: Introduction. Part II: Size range, external characters and teeth - Clarke, Robert; Anelio, Aguayo L; Obla, Paliza (Universitetsforlaget, 1968)
Keywords: Sørishavet; forskning; hvaler; marin biologi; oseanografi

On the tides at Norway Station and adjacent coastal areas of Antarctica - Hisdal, Vidar (Norsk Polarinstitutt. Skrifter, 1965)
Keywords: Den norske antarktisekspedisjonen 1956-60; Dronning Maud Land; ekspedisjoner; forskning; isshelf; observasjoner; oseanografi; tidevann